Предмет: Математика,
автор: Аноним
4)19-(2-18/3)=
5)-60/15+7*(6-14)=
6)-11*(5-9)-60/(-12)=
Ответы
Автор ответа:
0
19-(2-18/3)=19-2-6=11
-60/15+7*(6-14)=-4+7*(-8)=-4-56=-60
-11*(5-9)-60/(-12)=-11*(-4)+5=44+5=49
-60/15+7*(6-14)=-4+7*(-8)=-4-56=-60
-11*(5-9)-60/(-12)=-11*(-4)+5=44+5=49
Автор ответа:
0
5,6 реши пожалуста
Автор ответа:
0
спасибо
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Биология,
автор: sevenkez111
Предмет: Физика,
автор: Аноним
Предмет: История,
автор: YanaRusanova